THE HOMAGE TO DEBUSSY AT THE THÉÂTRE DES CHAMPS-ELYSÉES. Issue 3 (4th May 2018) - Blanchot, Maurice; Holland, Michael
Abstract: Michael Holland presents an early and little-known article by Maurice Blanchot, whose subject is the memorial concert in honour of Claude Debussy which took place in Paris in June 1932, following the unveiling of a monument to the composer earlier in the day. Blanchot provides a detailed account of the concert, emphasising the international co-operation that lay behind the expression of national pride, and arguing, against the grain of contemporary opinion, that the pure art of music transcends any notion of national genius.